Pengembangan Usaha Kerajinan Alat Musik Tradisional Batak Berbasis Digital Marketing Melalui Pejuang Muda - Samuel Pardede; Sinta Simanjuntak; Maidinse Hutasoit (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2022)
Pejuang Muda is a program for students to come down to the community who need helpby making social change through various activities. From designing to execution of relevant social programs for the area. Through this Pejuang Muda Program, students will be given the opportunity to directly apply their knowledge and provide social impact for the community, and play an active role as an agent of social change. Young Fighter Programfocusing on social entrepreneurship, which will give students the opportunity to gain experience infield and placed in priority areas including post-disaster areas, poverty areas, regional Remote Indigenous Community (RIC). The Pejuang Muda Program is an opportunity for students to implement the knowledge gained in college and actualize himself by plunging directly in the community. In addition, there is natural potential as well as human resources that can be extracted from underprivileged communities in the midst of their limitations. In this Pejuang Muda program,The Dalloid Art Studio community is the target group for the empowerment program.By analyzing existing resources and potential, the Pejuang Muda Humbang Hasundutan strives to increase productivity and work motivation of the Dalloid Art Studio community in making musikal instruments Batak tradition through developing, mentoring and training.